THE CHANGE IN EDUCATIONAL MANAGEMENT DUE TO INFORMATION TECHNOLOGY - Agus Leo Handoko (Adisam Publisher, 2024)
This extensive analysis of the literature delves into the various aspects of optimizing the role of information technology in the transformation of educational management. Examining how life is interconnected from the beginning to the end and how the expanding area of information technology might inspire a new way of living, this study summarizes the literature, highlights trends, and provides guidance for academics, educators, and policy makers. The need to understand how technology may replace human labor in the field of education by automating tasks or processes is the driving force behind this investigation. enhancing the human role by giving instructions, assignments, or procedures. altering or restructuring a job or procedure. Several topics are covered in this examination, beginning with the idea of.